Determination of Gear Bending Fatigue Limit based on Up and Down Method - Yang Guangming (Jixie chuandong)
The bending fatigue strength of gear is an important indicator for gear performance,and it is an effective method to obtain the bending strength according to the test procedure. The test of the single- tooth bending fatigue strength of 20 Cr Mo H carburized gear is discussed. The test method of pulse load in single-tooth and the group method is used in the experiment and the bending fatigue strength test of gear tooth at 5classes of constant stress levels is carried out on the electromagnetic resonance testing machine. By applying planar section method and broken- line section method,the root stress of gear teeth under different load levers is calculated. The macro morphology of fatigue fracture of gear test specimens is analyzed. The result shows that it is more actual to determine the risk position with broken- line section method. It provides a new approach for evaluating the gear bending fatigue strength.